Manifestaciones de la religiosidad mediterránea en la Protohistoria canaria (circa s. X a.n.e. al s. XV d.n.e.) - Atoche Peña, Pablo; Ramírez Rodríguez, Mª Ángeles (Gerión. Revista de Historia Antigua, 2009)
In this work, we present some ideas about cultural elements of the Canary Islands Protohistory, that were originated in the ancient Mediterranean which, after reaching the islands, were subjet of transformation, as a result of a cultural adaptation phenomenon. We visit some of the protohistoric canarian believings and religious behaviours, particularly concerned by their origins. From them it is possible to acquire their precedence and to study the particular adaptations produced after the settlement within the islands.